Contents of time orientation in preschool education - Živanović Milan V. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2017)
The paper presents the contents of the time orientation in preschool education. The absence of a specific sensory experience of time greatly complicates the possibilities of adopting time concepts, their relations and measurements. The way to overcome the problem is to tie up the characteristic activities and phenomena that children have mastered, for the peak concepts that need to be introduced. In the immediate work, the best results are achieved in an integrated approach to the problem, using a variety of methodical procedures and didactic material. It is necessary to use almost every situation that provides the opportunity to develop these concepts necessary for the normal inclusion of children in preparation for school and life in general. This provides an excellent basis for the productive cooperation of parents and educators. Today's children grow up in a close environment of ICT resources, and their measured and proper use helps in developing elements of time orientation.